Extensive Multifocal Emphysematous Osteomyelitis of Spine: A Rare Case and a Review of Literature - Sharma, Bhawna; Lakhanpal, Vikas; Goyal, Abeer; Shree, Ritu; Raj, Shashank; Sreenivasan, Priya; Biswal, Manisha; Ray, Pallab; Angrup, Archana (Infectious Disorders - Drug Targets, 2023)
Background: Emphysematous osteomyelitis (EO) is an extremely rare form of osteomyelitis which is complicated mainly by infection with gas-forming organisms. The common causative agents of this disease are mainly members of Enterobacteriaceae family, the most common are Escherichia coli and Klebsiella pneumoniae along with anaerobes. A total of 48 cases of EO have been reported in the literature till now globally and none have documented the isolation of Corynebacterium amycolatum. Case Presentation: We report a rare case of emphysematous osteomyelitis of the spine and pelvis due to Escherichia coli along with the isolation of Corynebacterium amycolatum from the same pus samples on two consecutive occasions in a 50-year-old female with uncontrolled diabetes mellitus, who was successively treated with antibiotics and drainage of pus. We also did a brief review of the literature of all cases reported till now. Conclusion: The role of Corynebacterium amycolatum in the etiology of emphysematous osteomyelitis needs to be evaluated further in future studies as we cannot completely ignore its isolation in two consecutive samples as a mere contaminant.
Keywords: Corynebacterium amycolatum